CD80 and CD86 Costimulatory Molecules Differentially Regulate OT-II CD4+ T Lymphocyte Proliferation and Cytokine Response in Cocultures with Antigen-Presenting Cells Derived from Pregnant and Pseudopregnant Mice - Tomasz Maj; Anna Slawek; Anna Chelmonska-Soyta (Hindawi Limited, 2014)
Immune phenomena during the preimplantation period of pregnancy are poorly understood. The aim of our study was to assess the capacity for antigen presentation of splenic antigen-presenting cells (APCs) derived from pregnant and pseudopregnant mice in in vitro conditions. Therefore, sorted CD11c+ dendritic cells and macrophages F4/80+ and CD11b+ presenting ovalbumin (OVA) were cocultured with CD4+ T cells derived from OT-II mice's (C57BL6/J-Tg(TcraTcrb)1100Mjb/J) spleen. After 132 hours of cell culture, proliferation of lymphocytes (ELISA-BrdU), activation of these cells (flow cytometry), cytokine profile (ELISA), and influence of costimulatory molecules blocking on these parameters were measured. We did not detect any differences in regulation of Th1/Th2 cytokine balance. CD86 seems to be the main costimulatory molecule involved in the proliferation response but CD80 is the main costimulatory molecule influencing cytokine secretion in pregnant mice. In conclusion, this study showed that CD80 and CD86 costimulatory molecules regulate OT-II CD4+ T lymphocyte proliferation and cytokine response in cocultures with antigen-presenting cells derived from pregnant and pseudopregnant mice. The implications of these changes still remain unclear.